Plant pathogens associated with Dieffenbachia oerstedii and Sygonium podophyllum in banana plantations in Costa Rica. - Brenes-Prendas, Steven; Wang-Wong, Amy; Agüero-Alvarado, Renan (Agronomía Mesoamericana, 2012)
The objective of this work was to analyze the presence of pathogenisc agents associated to field symptoms observed on D. oerstedii and S. podophyllum, treated with herbicides and untreated, studied from February to November of 2007, at Limofrut C banana farm, Matina,Costa Rica. Samples from symptomatic tissue of bothspecies were taken to the laboratory. Pseudomonas sppand Erwinia spp were found on samples from D. oerstediitissue; Xanthomonas spp were found on samples from S.podophyllum symptomatic tissue. Fluorescent Pseudomonas bacteria were detected on samples from non symptomatic D. oerstedii tissue.